The Requirements to the Modern Foreign Languages Teacher of Tertiary Institutions - Н. В. Майєр (Іноземні мови, 2013)
The paper presents the requirements to the modern foreign language teacher according to the current trends in the organization of the foreign languages teaching in tertiary institutions. The components of professional competence of foreign languages teachers have been analyzed. The importance of the methodological competence has been stated. The media and ICT competences are proved to be acquired by modern university teachers.